Examining the role of AI ethics in establishing Human-AI Workplace Coexistence in a selected Telecommunications Organisation in South Africa - Muir, Elmarie (University of the Witwatersrand, Johannesburg, 2024)
Artificial Intelligence technologies reinvent how we live, work, and organise our daily lives and social interactions. It brings about operational efficiencies, customer service enhancements, and organisational innovations for organisations, redefining the future landscape that will open new dimensions beyond distance, distortion, and space. Despite these benefits, using AI raises enormous concerns for telecommunication organisations beyond data protection and security vulnerabilities, including introducing ethical dilemmas due to the technology's accountability, transparency, algorithmic bias, explainability issues, and the potentially dire ramifications for employment. These issues inherent in AI technology and its concerns make it necessary to explore the ethical considerations and the role of AI ethics in establishing a harmonious human-AI workplace coexistence in the telecommunications workplace. A qualitative methodology was undertaken with purposively selected participants based on their telecommunications industry experience and exposure to AI technologies in the organisation, which allowed participants to be interviewed to gain insights into their perspectives. The research findings show that employees have real job insecurities for their future and their technological readiness to work alongside this technology. Key themes highlighted ethical AI practices, with participants advocating for transparency and accountability. Trust in the organisation and trust in AI technology, with proactive engagement with employees and stakeholders, are pivotal to mitigating their concerns and creating a conducive environment for successful integration. Furthermore, upskilling is vital for establishing trust in AI. In conclusion, the consensus is that although ethical guidelines are essential, more than ethics alone may be required to establish human-AI workplace coexistence. Instead, the organisation should cultivate an organisational culture iii that supports ethical AI practices with a robust governance framework to ensure adherence to ethical guidelines is followed and responsible use of AI. Furthermore, leaders must ensure openness and transparency about their intentions to adopt AI, foster trust in the organisation that AI strategies are not designed to replace workers and develop the necessary technological competencies through targeted skill development to build trust in the technology. This will allow the organisation to be successful in their AI adoption journey and establish collaborative intelligence for harmonious human-AI workplace coexistence.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Artificial Intelligence; Worker; Workplace; Coexistence; Ethics; Trust; Collaborative Intelligence, Skills; UCTD; SDG-8: Decent work and economic growth